Hubungan Kekerabatan Bahasa Nafri dan Bahasa Sentani - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
A common way used to determine the language of kindship is the study kindship based on promary secondary correspondence, kognat data (same, both meaning and form), and relationships at the llevel of the phrase. Specifically studied in this paper is about the level of the phrase. Furthermore, the level of relationship is the study of syntactic phrases. One of the elements which form the level of syntactic phrases in a language is the numeralized and measure. This paper describes the kindship relation between language of Nafri and Sentani based on numbers and measure phrases.